Microstructure & Mechanical Properties Evaluation of Al6082 /AlSi10Mg Composite for Light Weight Structural Applications - Burlakanti Subramanyam; Pitchaipillai Periyasamy (Mechanics of Advanced Composite Structures)
The main objective of this research work is to provide lightweight and high-strength materials for structural engineering applications. In general, the mechanical properties of pure Al6082 components are less as compared to the AlSi10Mg components. This work aims to study and improve the mechanical properties of the Al6082/AlSi10Mg composite. The composite, produced by the stir casting technique, stands out for its mechanical performance and microstructure. The findings shed light on the composite's suitability for different uses in sectors like aerospace, automotive, and marine. The outcomes of microstructure and mechanical properties can give significant evidence about whether a composite is appropriate for a given application. This data can be used to make well-informed choices about the composite's suitability for particular applications and to direct future advancements in its mechanical strength. The experimental work was carried out with the composition of Al6082 raw material and AlSi10Mg fresh powder. The weight percentage (Wt. %) of AlSi10Mg is considered with 0.5 % for sample S1, 1.0 % for sample S2, and 0.0 % for sample S3. The microstructure analyses performed that, the S1 sample showed fine microstructure with major porosity, the S2 sample showed coarse structure with minor porosity and the S3 sample showed fine microstructure with minor porosity. The microstructural investigation shows that the silica particles were evenly distributed throughout the aluminum matrix, which ensured that the composites' ultimate tensile strength, hardness, and impact strength had been increased. The mechanical properties of samples are evaluated with tensile, compression, impact, and hardness tests.  The tensile strength of the S2 sample (127 MPa) is high as compared to the S1 sample (110 MPa) due to less porosity, fine grain microstructure, and high Ti element presence in the S2 sample. The compressive strength of the S2 sample (143.3 MPa) is high as compared to the S1 sample (117.1 MPa) due to the fine grain microstructure and high Ti element in the S2 sample. The impact strength of the S2 sample (4.4 J) is high compared to the S1 sample (4.0 J). The microhardness tested at 0.5 Kgf load, 63.7 HV for the S1 sample, 65.1 HV for the S2 sample, and 46.3 HV for the S the 3 sample. Further, the microhardness test was conducted at 1.0 Kgf load., the values are 54.7 HV for the S1 sample, 59.7 HV for the S2 sample, and 38.3 HV for the S3 sample. From the findings, it is stated that the S2 sample performed an excellent mechanical property as compared to the S1 and S3 samples due to more wt. % of Ti and Al in the S2 sample. SEM examination revealed that the S1 sample has more pits and cracks as compared to the S2 and S3 samples. SEM, EDS, and XRD analyses were performed and displayed outstanding results. XRD analysis revealed the same elemental presence of EDS analysis.  The research work is carried out in a systematic procedure and a comparison is made of the test results with the available existing results by the researchers.  Compared to other compositions of available existing research work this Al6082 / AlSi10Mg is also suggestable for the development of lightweight structural applications.